Iterative detection of multicode DS-CDMA signals with strongly nonlinear transmitters - Dinis, Rui (2013)
Whenever a DS-CDMA signal is the sum of several components associated to different spreading codes it has high envelope fluctuations and a high peak-to-mean envelope power ratio (PMEPR) setting strong linearity requirements for the power amplifiers. The use of clipping and filtering techniques (which can be repeated several times) was shown to be an effective way of reducing the PMEPR of DS-CDMA signals. We consider an improved receiver where there is an iterative estimation and cancelation of nonlinear distortion effects. The proposed receiver allows significant performance improvements after just a few iterations, even when we have strong nonlinear distortion effects.